Effect of salt reduction interventions in lowering blood pressure: A comprehensive systematic review and meta-analysis of controlled clinical trials. - Soghra Aliasgharzadeh; Jafar Sadegh Tabrizi; Leila Nikniaz; Mehrangiz Ebrahimi-Mameghani; Neda Lotfi Yagin (PLoS ONE, 2022)
Background Excessive salt intake results in hypertension (HTN), which is a major risk factor for cardiovascular disease (CVD). This review and meta-analysis aimed to evaluate the effect of salt reduction interventions on systolic blood pressure (SBP) and diastolic blood pressure (DBP). Methods Studies were identified via systematic searches of the databases, including PubMed, Embase, Scopus, and Web of Science. All the studies examining the effectiveness of salt reduction interventions on blood pressure (BP), regardless of age, sex, and HTN status, were included in the systematic review, and eligible studies were used in the meta-analysis. A random-effect model was applied for quantitative data synthesis. Results A total of 50 trials extracted from 40 articles (21 trials on nutrition education,10 on self-help materials,17 on salt substitutes, and 2 on food reformulation) were included in the systematic review. The pooled results of 44 eligible trials showed that salt substitution and nutrition education interventions had significant effects on both SBP (WMD: -7.44 mmHg, P<0.001 and WMD: -2.75 mmHg, P<0.001, respectively), and DBP (WMD: -3.77 mmHg, P<0.001 and WMD: -2.11 mmHg, P<0.001, respectively). Furthermore, using self-help materials led to a significant reduction in SBP among subjects aged 25-60 years (WMD: -2.60 mmHg, P = 0.008); it also decreased both SBP and DBP among those who were hypertensive (WMD: -3.87 mmHg, P = 0.003 and WMD: -2.91 mmHg, P<0.001, respectively). Conclusion Our results supported that salt substitution and nutrition education are effective nutrition strategies to lower BP. It seems that multi-component approaches could be more effective in improving BP status. However, further trials are required.